Pengaruh Motivasi dan Disiplin Kerja Terhadap Kinerja Pegawai - Khoirul Insan,; Tarjo Tarjo,; Hasdani Hasdani, (Manajemen Kreatif Jurnal, 2024)
: Human resources are the main driver in an organization, the progress and decline of an organization is determined by the existence of its human resources. So that human resources or employees in an organization become an important concern in achieving organizational success. The purpose of this research is to determine the influence of work discipline and discipline on the performance of Bungo Regency Housing and Settlement Area Service employees. This research uses a quantitative approach with an associative type of research. The population of this study were all employees of the Bungo Regency Housing and Settlement Area Service using a sampling technique with a total sampling of 37 employees. Questionnaire data collection and data analysis used multiple linear regression analysis using the SPSS Statistics version 23 application.The research results show that the motivation variable partially has a significant effect on employee performance, with a significant level of 0.017 ≤ 0.05 or tcount of 2.522 ≥ ttable 2.030. The work discipline variable partially has a significant effect on employee performance, with a significant level of 0.001 ≤ 0, 05 or tcount of 3,749 ≥ ttable 2,030. The variables of motivation and work discipline simultaneously have a significant effect on employee performance, with a significance level of 0.000 ≤ 0.05 or fcount of 18.939 ≥ ftable 4.130.